Vitamin D status and serum vitamin D binding protein levels in Nigerian children with nephrotic syndrome - Solarin, Adaobi U; Adekunle, Motunrayo O; Oladimeji, Alaba B; Olutekunbi, Olanike A; Lamina, Moriam O; Oshomah-Bello, Oluwatosin E; Adetola, Olamide I; Animasahun, Barakat A; Njokanma, Olisaemedua F (African Journal of Nephrology, 2022)
Introduction: Nephrotic syndrome is a chronic relapsing condition associated with urinary loss of albumin and other proteins such as vitamin D binding protein (DBP). We determined vitamin D status and serum DBP levels in children with nephrotic syndrome and compared them to healthy controls. Methods: A cross-sectional study was performed over a six-month period in children less than 18 years of age. The children with nephrotic syndrome were categorised by disease status as either newly diagnosed, in remission, resistant to therapy, or in relapse. Vitamin D levels were regarded as sufficient if ≥75 nmol/L, insufficient if <75 nmol/L but ≥50 nmol/L, deficient if <50 nmol/L, and severely deficient if <25 nmol/L. Serum DBP was also measured. Results: Fifty-five children with nephrotic syndrome and 24 controls were included in the study. There was no significant difference between the median ages of the cases (72.0 months, interquartile range (IQR) 48.0–120.0 months) and the controls (84.0 months, IQR 39.0–129.0 months). Severe vitamin D deficiency, deficiency and insufficient levels were documented in 54.5%, 41.8% and 3.6% of cases, respectively, significantly lower than the controls (P = 0.003). Vitamin D levels were higher in children with nephrotic syndrome in remission than in those who were not (30.3 ± 15.2 nmol/L vs 19.6 ± 11.0 nmol/L, P = 0.004). In the groups who were in remission, newly diagnosed, relapsing, and resistant, the median vitamin D levels were 30.3 nmol/L, 20.1 nmol/L, 19.2 nmol/L and 9.4 nmol/L, respectively (P = 0.031). Conclusions: Hypovitaminosis D occurs frequently in Nigerian children with nephrotic syndrome as well as in apparently healthy controls. Routine supplementation of vitamin D should be considered in children with nephrotic syndrome irrespective of whether the disease is in remission or not, or whether it is steroid-sensitive or not.